Skrining Fitokimia Sayur Bening Daun Kelor (Moringa Oleifera) - Yopi Suryatim Pratiwi; Sri Handayani; Yesvi Zulfiana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction: The mortality rate is an important health indicator and reflects the degree of health in an area. The Infant Mortality Rate (IMR) in Indonesia is still high. The infant mortality rate is largely due to nutritional factors. Some diseases that arise due to malnutrition include pneumonia, diarrhea, and perinatal. Exclusive breastfeeding can reduce infant morbidity and mortality. The most common reason found in breastfeeding mothers who stop breastfeeding is due to insufficient milk production. Utilization of plants/vegetables such as Moringa Oleifera is often used by the community to increase milk production. The most widely used processing of Moringa Oleifera by nursing mothers is to make it a clear vegetable. The aim of this study was to screen for phytochemicals on the clear vegetables of Moringa Oleifera. Methods: The method in this study was to carry out laboratory tests on clear vegetable Moringa Oleifera consisting of 150 grams of Moringa Oleifera, 750 cc of water, and salt to taste. Alkaloid screening used Mayer's and Dragendorff's reagents, while steroids used acetic acid, anhydrous and concentrated H2SO4 reagents. Results: The results showed that the clear vegetable of Moringa oleifera showed the content of alkaloid and steroid compounds. Conclusion: Utilization of clear vegetable moringa leaves is an alternative that can be used to overcome the problem of insufficient milk production, besides being cheap and easy to obtain. Suggestion: Future researchers are advised to conduct research that can be directly applied to breastfeeding mothers to prevent failure of exclusive breastfeeding due to insufficient milk production.